Innovative Integrated Science Learning by Integrating Southern Tapanuli Traditions - Eni Sumanti Nasution; Kasmawati; Evitamala Siregar; aisyah; Rizki Fadilah (PT Inovasi Pratama Internasional, 2024)
The integration of local traditions into science education has the potential to enhance student engagement, cultural relevance, and academic performance. This study explores the development of an innovative integrated science curriculum that incorporates the rich cultural heritage of Southern Tapanuli, Indonesia. The research employs a qualitative approach, utilizing purposive sampling to select approximately 30 participants, including teachers, students, and community members. Data collection involves semi-structured interviews, classroom observations, and document analysis. Thematic analysis reveals five key themes: Cultural Relevance (107 mentions), Engagement (127 mentions), Community Involvement (71 mentions), Practical Applications (39 mentions), and Challenges (31 mentions). Content analysis further highlights the importance of cultural context (30.7%) and participant interaction (36.0%). Comparative analysis indicates significant differences between groups, with Group A demonstrating higher mean scores (82.5 vs. 75.2, p<0.05) and success rates (78% vs. 65%, p<0.01). Inferential statistics, including t-tests (t=2.45, p=0.018), ANOVA (F=4.67, p=0.012), and chi-square tests (χ²=10.30, p=0.015), support the existence of significant differences and associations between variables. These findings align with previous research emphasizing the benefits of interactive teaching methods and community engagement in education. The study concludes that culturally responsive teaching approaches and community involvement can significantly enhance student motivation and achievement in science education. Future research should further explore these relationships in diverse educational settings to validate and extend these findings.